If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 7(-7 + -5n) = 0 -4 + (-7 * 7 + -5n * 7) = 0 -4 + (-49 + -35n) = 0 Combine like terms: -4 + -49 = -53 -53 + -35n = 0 Solving -53 + -35n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + -35n = 0 + 53 Combine like terms: -53 + 53 = 0 0 + -35n = 0 + 53 -35n = 0 + 53 Combine like terms: 0 + 53 = 53 -35n = 53 Divide each side by '-35'. n = -1.514285714 Simplifying n = -1.514285714
| -4u-3=9(u+4) | | -8(4+n)-8= | | 11x=222 | | 0.22y+0.03(y+4000)=2370 | | 3c+9c= | | q-9=-19 | | 4v-15=49 | | -9(v-4)=5v+4 | | .4x-73=90 | | -8(4+n)= | | 9-9=-19 | | 5+-(11)-(-11)= | | 15u+5v-3u+17v= | | -19+p=-9 | | 7(2x-10)-3=7(x-5)+4 | | -19+p=9 | | 8=16.9-a | | cosine(x)=-0.25 | | 8x-4(1+X)= | | 10=.11(0)+b | | X*x+1=101 | | 6/5÷6/ | | 2x+3+x=128 | | F(x)=log(x+7)+4 | | 6/5÷6/8 | | 7x-6+10x-5= | | 3c+12=5c+11.44 | | 6(-7d+12d)= | | -6w+8=-2(w+8) | | -25+n=-37 | | g(x)=x-13 | | (-5)(3)(-3)= |